PENGARUH MANAJEMEN PEMBIAYAAN PENDIDIKAN DAN FASILITAS PEMBELAJARAN TERHADAP MUTU SEKOLAH : Penelitian pada SMK Swasta Se- Korwil III Kabupaten Bandung - Lilis Ida Nurlaya (STAI Pelabuhan Ratu, 2020)
School quality is directly related to the quality of education in an education unit. In achieving good school quality, it is necessary to pay attention to teacher quality, student quality, school culture and discipline, and educational facilities and funding. This study focuses on studying how the influence of education funding management and learning facilities on school quality. The aim is to find out the description and analyze the influence of education funding management and learning facilities on school quality. This study uses a descriptive method with a quantitative approach. Sampling of 10 heads of Private Vocational Schools in KORWIL III Bandung Kabuaten. The analysis technique uses descriptive analysis and inferential analysis. The results of this study indicate that the influence of education financing management and learning facilities on school quality together provide a strong and significant influence. amounting to 38.5%, meaning that management of education funding and learning facilities are related simultaneously and significantly to the quality of schools. While the remaining 61.5% is determined by other factors not explained in this study.